Vertical variations in microbial diversity, composition, and interactions in freshwater lake sediments on the Tibetan plateau - Zhu, Xinshu; Deng, Yongcui; Huang, Tao; Han, Cheng; Chen, Lei; Zhang, Zhigang; Liu, Keshao; Liu, Yongqin; Huang, Changchun (Frontiers in Microbiology, 2023)
Microbial communities in freshwater lake sediments vary with depth. Further exploration is required to understand their biodiversity pattern and microbial interactions in vertical sediments. Here, on the Tibetan plateau, sediment cores from two freshwater lakes, Mugecuo (MGC) and Cuopu (CP), were sampled and subsequently sliced into layers at a depth of every centimeter or half a centimeter. Amplicon sequencing was used to analyze the composition, diversity and interaction of microbial communities in these vertical sediments. We found that sediment samples of both lakes could be clustered into two groups at a sediment depth of about 20 cm, with obvious shifts in the microbial community compositions. In lake MGC, the richness component dominated the β-diversity and increased with depth, indicating that the microbial community in the deep layer of MGC was selected from the surface layer. However, in lake CP, the replacement component dominated the β-diversity of vertical sediment, implying a high turnover rate in the surface layer of CP and inactive seed banks with a high variety in the deep layer. Co-occurrence network analysis demonstrated that negative microbial interactions predominated in the two lake surface layers with high nutrient concentrations, while positive microbial interactions were more common in deep layers with low nutrient concentrations. This finding suggested that microbial interactions are influenced by the nutrient conditions of the vertical sediments. Additionally, abundant taxa and rare taxa provided important contributions to microbial interactions and vertical fluctuation of β-diversity, respectively. This work deepens our understanding of patterns of microbial interactions and vertical fluctuation of β-diversity in lake sediment columns, particularly in sediments from the Tibetan Plateau.